Las revistas de museos y museología en español y portugués: una exploración panorámica a ambos lados del Atlántico - Lorente, Jesús-Pedro (Anais do Museu Paulista: História e Cultura Material, 2013)
This article offers a historical account of journals specializing in museums and museology in Spain, Hispanoamerica, Brazil and Portugal. This sampling shows a growing abundance and variety, which corroborates the great development attained by Museology as a discipline. But most authors and readers of these publications tend to be from their respective countries or cultural area. This reinforces the need for museology journals universally known and recognized, even out of the countries where Spanish and Portuguese are official languages.